THE PREDISPOSING FACTORS OF PIRIFORMIS SYNDROME: STUDY IN A REFERRAL HOSPITAL - Siahaan, Yusak Mangara Tua; Ketaren, Retno Jayantri; Hartoyo, Vinson; Tiffani, Pamela (Malang Neurology Journal, 2019)
Background: Piriformis syndrome is a neuromuscular condition characterized by hip and gluteal pain caused by abnormality of piriformis muscle. In clinical practice, this syndrome is usually misdiagnosed with other spinal disorders. There is no specific test in diagnosing piriformis syndrome, therefore by understanding the characteristics and predisposing factors, clinicians may be more aware in diagnosing this syndrome. Objective: To investigate the characteristics and predisposing factors of piriformis syndrome.Methods: A descriptive study was conducted on patients with gluteal pain in a referral hospital. Diagnosis was established by block injection on piriformis muscle and showed clinical improvement afterwards. Demographic characteristics, predisposing factors, and physical examination were analyzed. The data is collected and processed by SPSS 20.0.Results: The total of 65 patients were evaluated, with a male to female ratio 1:3. As much as 47.7% of patients were > 60 years old. Average weight was 60 kg and BMI (Body Mass Index) was within normal range (58.9%). Most subjects were housewives (55.4%) and the majority of subjects had history of microtrauma such as sitting on rigid surfaces (36.9%), walking or running long distances (18.5%), and cross-legged sitting (10.8%). Average sitting per day was approximately 5 hours. In 56.9% of subjects, exercises were conducted. There was no history of back pain in 81.5% of subjects.Conclusion: Our study showed age and housewives characteristics differ with other studies. The most predisposing factors were history of microtrauma, female, age, and normal BMI.